Educación y gestión en América Latina - José Solano-Alpízar (Universidad Nacional, Costa Rica, 2005)
Descriptive exercise that addresses the topic of Education Management in Latin America. It gives a general view of the socio-historical context in which this management has taken place. The article first presents the development model spread by CEPAL (Spanish acronym for the Economic Commission of the UN for Latin America and the Caribbean) in Latin America after the second half of the twentieth century and its influence in shaping the educational model adopted by different countries of the region. Then, we review the road traveled by the educational management process during the following decades. Finally, there is a brief description of the most important transformations this management has had after the challenges encountered during the beginning of the twenty-first century.